2021
DOI: 10.1186/s12903-021-01812-9
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the sex hormones’ serum level in women with recurrent aphthous stomatitis and healthy population: a cross-sectional study

Abstract: Background In this study, we aimed to evaluate the sex hormonal serum level in patients with recurrent aphthous stomatitis and compare them with healthy participants. Methods This cross-sectional study was done on patients with recurrent aphthous stomatitis who had referred to Shiraz Dental Faculty, Oral and Maxillofacial Medicine Department during 2018–2019. The non -menopause women with recurrence of at least 3 lesions per year were enrolled in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…A cross-sectional study did not find significantly abnormal estradiol levels in women with recurrent aphthous stomatitis. [18] And B E McCartan thought there was no association between aphthous stomatitis and the premenstrual period, pregnancy, or menopause with fluctuating hormonal status. [24] These studies are not consistent in supporting the association between estradiol and mouth ulcers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A cross-sectional study did not find significantly abnormal estradiol levels in women with recurrent aphthous stomatitis. [18] And B E McCartan thought there was no association between aphthous stomatitis and the premenstrual period, pregnancy, or menopause with fluctuating hormonal status. [24] These studies are not consistent in supporting the association between estradiol and mouth ulcers.…”
Section: Discussionmentioning
confidence: 99%
“…However, the evidence supporting this association was inconsistent with other studies which had shown no significant association. [18] There are conflicting accounts of the role of estradiol in mouth ulcers maybe due to the lack of clinical large sample size trials. In addition, some confounders containing unmeasured risk factors in existing trials cannot be completely ruled out.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, there are three types of RAS (minor, major, and herpetic forms) that can be clinically identified [ 1 ]. The main causes of RAS are unknown; however, some triggers for RAS outbreaks are introduced such as emotional stress, deprivation of sleep, trauma, lack of different types of vitamin B, iron and folic acid deficiencies, menstruation, anemia, and fluctuation of sex hormones in women [ 2 , 3 ]. Nevertheless, the most common treatment for RAS is symptom therapy which is focused on reducing pain [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Due to the aforementioned properties of Rhus coriaria, the effect of its extract has already been investigated in many different studies on oral environment [2][3][4][5]. On this basis, in a study by Kermanshah et al.…”
Section: Introductionmentioning
confidence: 99%
“…Menstruation is a crucial physiological manifestation in the life of a woman, the hypothalamus-pituitary-ovarian axis should be actively coordinated for natural menstruation to occur. The endometrium must be sensitive to ovarian hormones, and the inflow tube must be patent; any disruption in any of these elements causes problems (Lavaee et al,2021). The ovarian secretion of estrogen and progesterone diminishes throughout the menopausal transition.…”
Section: Introductionmentioning
confidence: 99%